Extraperitoneal cesarean section: a retrospective analysis - Sharma, Partha Pratim; Gond, Sneha; Ansari, M. D. Kamaluddin; Madhuri, Narra; Bera, Surendra N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Morbidity of caesarean section still persist in terms of pain, infection and adhesion. This study will focus on different morbidities associated with ECS. Methods: A retrospective analysis of 29 ECS were included from June to September 2018, done at Midnapore Medical college, West Bengal, India. Results: Contracted pelvis (12/29, 41.37%) and cephalopelvic disproportion (10/29,34.48%) were common indications for ECS. Mean gestational age was 39.65±1.31 weeks and birth weight were 3.01±0.40 kg. Time taken for ECS was 33.06±10.85 minutes. Extension of uterine incision and mild distension of abdomen occurred in 3.44% each. Post-operative period was uneventful and all discharged after 72 hours of operation. Conclusions: ECS can be performed safely by experienced hands with less feto-maternal morbidity and early discharge of mother and baby.